Shrinkage stress, long-term adaptation and bond strength of low-shrinkage composite resins. (March 2016) - Di Francescantonio, M.; Boaro, L.C.C.; Arana-Chavez, V.E.; Braga, R.R.; Giannini, M.
Abstract: Purpose: To evaluate the internal adaptation, bond strength, and polymerization stress of silorane- and methacrylate-based composite resins. Material and methods: Three methacrylate-based composite resins (Heliomolar; Tetric N-Ceram and Aelite LS) and one silorane-based composite resin (Filtek Silorane) were tested. Polymerization stress ( n =5) was determined by the insertion of the composite resin between rods of polymethyl methacrylate. The ratio of the maximum force of contraction was recorded and the cross-sectional area of the rod was used to calculate the nominal stress. Bond strength was evaluated by microtensile bond test. Dentin surfaces of human third molars were bonded, sectioned, and stored for 24 h or 1 year in distilled water before the bond strength test. The ratio of maximum force and the adhered area was used for the bond strength calculation. For internal adaptation analysis, third molars received Class II cavities and were restored according to either an incremental oblique or bulk-filling technique. After being sectioned perpendicularly, impressions were taken and epoxy resin replicas were obtained of the internal surfaces of the restorations (after 24 h and 1 year of storage) to analyze gap formation using scanning electron microscopy. Results: Filtek Silorane showed the highest​ bond strength after one year of storage, the lowest formation of gaps, and polymerization stress similar to methacrylate-based materials. Conclusion: Silorane restorative material presented polymerization stress comparable to that of methacrylate-based composite resins, stable dentin bond strength after one year and better internal adaptation to the cavity walls, showing good alternative to traditional composite resins and promising longevity.